A persona do líder : estudo socioantropológico sobre a construção social da liderança em uma organização de saúde em Porto Alegre - Souto, Caroline Buratto (2016)
Understanding the trajectory of leadership in organizations is the main objective of this dissertation. By exploring the leadership theme is intended to expose some person's sense and identity concepts, through the analysis of social time and their impact on identity. Furthermore, the analysis of the leadership literature in Administration and conversations with leaders of a health organization, helped to answer the main objective of this research. The ethnographic study and interviews about the path of people in formal positions of leadership demonstrate how this construction occurs in practice and how the social roles played by one person complement and assist the reflections and lessons that led these leaders their current positions .